Modeling the Impact of Double‐Dose Vaccination and Saturated Transmission Dynamics on Mpox Control - Fredrick Asenso Wireko; Joshua Nii Martey; Isaac Kwasi Adu; Bright Emmanuel Owusu; Sebastian Ndogum; Joshua Kiddy K. Asamoah (Engineering Reports)
ABSTRACT This study constructs a compartmental model that incorporates the dynamics of implementing a double‐dose vaccination for the Mpox disease. The study further explores the pattern of saturated transmission dynamics of the Mpox disease. This model was studied through the Caputo fractional derivative as the Mpox disease has been shown to have memory dynamics. We discussed the existence and uniqueness of the Mpox disease model. Again, through the Hyers‐Ulam and Hyers‐Ulam‐Rassias stability criteria, we have shown that the model is resilient to unexpected changes in the population. A thorough sensitivity study was performed on the model. It was observed that the effective implementation of the double‐dose vaccination and minimizing direct contact between the infected and the uninfected could help eradicate the Mpox disease from the population. In the numerical simulation section, the dynamics of the memory effect in the model were explicitly exhibited as the disease continuously declined whenever ω=0.80. Finally, we have shown that an effective implementation of isolation and treatment measures contributes massively to controlling the Mpox disease in the population.